Pelatihan Creative Design Dengan Canva Bagi Karang Taruna Di Kelurahan Pancoran Mas Depok - Zulkarnain, Iskandar; Fauziyah, Fauziyah (LPPM Universitas Bung Karno, 2022)
Technology development and advancement, especially Indonesia as a country that has a lot of natural and human resource potential, cannot be equated with developed countries. Therefore, the knowledge possessed will be shared so that it can be useful for the community, by holding an introduction to the Canva application. Canva is an online graphic design that's easy to use, even for beginners. Not only that, But Canva can also be accessed via desktop and mobile devices. Thus, training related to the Canva application is carried out and it is hoped that this knowledge can improve the ability of Karang Taruna friends to be more creative and creative.